Database Models in Agriculture: a systematic review - Carvalho, Herica Fernanda de Sousa; Bezerra, Luiza Maria Capanema; Rosa, Ferrucio de Franco (Cadernos de Ciência & Tecnologia, 2025)
Access to organized agricultural information represents a trend in the development of modern agriculture. Synthesis and analysis of the literature on data models used in agricultural databases can guide future decision making. In this study, we present a systematic review covering the period from 2010 to 2023, using keywords in scientific databases to identify recent approaches in agriculture using database models. We identified several approaches involving modeling, integration, and management of agricultural data. This review provides a comprehensive overview of the latest methodologies, presenting studies that examine data models specific to agriculture, with an emphasis on the area of plant breeding. Besides, techniques and methods available in the literature that can be used in building databases — considering specific needs for making decisions on agricultural data — are pointed up.